AHCC® Supplementation to Support Immune Function to Clear Persistent Human Papillomavirus Infections - Smith, Judith A.; Gaikwad, Anjali A.; Mathew, Lata; Rech, Barbara; Faro, Jonathan P.; Lucci, Joseph A.; Bai, Yu; Olsen, Randall J.; Byrd, Teresa T. (Frontiers in Oncology, 2022)
OBJECTIVE: To determine the efficacy, safety, and durability of use of AHCC supplementation for six months to support the host immune system to clear high risk HPV infections. STUDY DESIGN: This was a randomized, double-blind, placebo-controlled study (CTN: NCT02405533) in 50 women over 30 years of age with confirmed persistent high-risk HPV infections for greater than 2 years. Patients were randomized to placebo once daily for 12 months (N=25) or AHCC 3g by mouth once daily on empty stomach for six months followed by six months of placebo (N=25). Every 3 months patients were evaluated with HPV-DNA and HPV-RNA testing with blood sample to evaluate a panel of immune markers including: interferon-alpha, interferon-beta (IFNβ), interferon-gamma (IFN, IgG1, T-lymphocytes, and natural killer (NK) cell levels. RESULTS: Fifty women with high-risk HPV were enrolled and 41 completed the study. Fourteen (63.6%) of the 22 patients in AHCC supplementation arm were HPV-RNA/HPV-DNA negative after six months with 64.3% (9/14) achieving a durable response defined as being HPV-RNA/HPV-DNA negative six months off supplementation. On placebo arm, two (10.5%) of 19 patients were HPV negative at 12 months. Twelve patients completed the un-blinded study and 50% (n=6) were HPV-RNA/HPV-DNA negative after six months of AHCC supplementation. Combining all 34 participants that received AHCC supplementation gives an overall response rate of 58.8% that cleared HPV persistent infections. At time of enrollment the mean IFN level was 60.5 ±37.6pg/mL in women with confirmed persistent HPV infections. Suppression of IFNβ to less than 20pg/mL correlated with increase in T-lymphocytes and IFN and durable clearance of HPV infections in women that received AHCC supplementation. CONCLUSION: Results from this phase II study demonstrated AHCC 3g once daily was effective to support the host immune system to eliminate persistent HPV infections and was well tolerated with no significant adverse side effects reported. The duration of AHCC supplementation required beyond first negative result needs more evaluation to optimize success for durable outcomes. The suppression of the IFN-β level to less than 20pg/mL correlated with clearance of HPV infections and merits further evaluation as a clinical tool for monitoring patients with HPV infections.